A Scale for Early Detection of Children with Learning Problems. - Novack, Harry S.; Bonaventura, Elisa; Merenda, Peter F. (Exceptional Children, 1973)
The Rhode Island Pupil Identification Scale, which is a pupil behavior observation scale for use by classroom teachers, is discussed. The scale is a multipurpose instrument designed to improve communication among the educator and his colleagues in the other child centered professions. The standardization sample comprised 851 pupils in kindergarten through second grade drawn from 7 schools in 3 school districts in Rhode Island. Retest reliabilities and several validity studies are reported, and the findings of the studies attest to the concurrent and predictive validities of the scale.